KEMAMPUAN MENARI SIGEH PENGUTEN PADA SISWA KELAS XI IPA 3 DI SMA YP UNILA BANDAR LAMPUNG - Freny oktaviana; Fitri daryanti; Ni Nyoman wetty; susi wedhyaningsih (Jurnal Seni dan Pembelajaran, 2013)
ABSTRACTThe problem that discussed in this research was dance ability of sigeh penguten of student at the second grade of SMA YP Unila Bandar Lampung. The aim of the research was to describe the students activity in lerning sigeh penguten dance and to describe the students ability in dancing sigeh panguten. That is terms of three indicators, they were wiraga, wirama, wirasa.The method that used in this research is descriptive. The data collection that used in this research were observation, interview, and documentation. The source of data in this research were students of XI IPA3 SMA YP Unila that there are 39 students 24 female students and 15 male students.Based on the technique of data analysis, by seeing from the students activities which is divided into four aspect they are visual activities, listening activities, motor activities, and emotional activities with the score presentage 70 % for the first meeting and the criteria was enough, 70% for the second meeting, the criteria good, 70 % for the third meeting and the criteria was enough. 70% for the fourth meeting which is enough as the criteria, and 85 % for the fifth meeting with very good as the ctiteria. By seeing from the students dance ability based on the result of the observation in the sheet of practice test, it can be seen that the abilities of the students of IX IPA3 SMA YP Unila in dancing sigeh penguten dance in the class is enough. It can be seen from the average of students abilities in practicing the sigeh penguten dance. The score was 68. That was based on the abilities in every aspect they are the step of movement with the percentage is 66% it was enough, the aspect of movement technique with the percentage is 66 % it was enough, the aspect of movements correctness with the music with the score percentage is 72% it was enough, and the aspect of expression when they danced with the score percentage is 67% and it was enough.KEY WORD: EDUCATION, ABILITY, SIGEH PENGUTEN DANCE,